2020
DOI: 10.1186/s13613-020-00672-w
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis at ICU admission does not decrease 30-day survival in very old patients: a post-hoc analysis of the VIP1 multinational cohort study

Abstract: Background: The number of intensive care patients aged ≥ 80 years (Very old Intensive Care Patients; VIPs) is growing. VIPs have high mortality and morbidity and the benefits of ICU admission are frequently questioned. Sepsis incidence has risen in recent years and identification of outcomes is of considerable public importance. We aimed to determine whether VIPs admitted for sepsis had different outcomes than those admitted for other acute reasons and identify potential prognostic factors for 30-day survival.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Proportions and ICU-mortality rates of VIPs admitted with sepsis found in our study were comparable with those found in the previous VIP-1 study [2]. A systematic review, including 18 studies and 4,256 patients aged ≥80 years admitted to the ICU with sepsis, reported ICU, hospital and 1-year mortality rates of 43%, 47% and 68%, respectively [3].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Proportions and ICU-mortality rates of VIPs admitted with sepsis found in our study were comparable with those found in the previous VIP-1 study [2]. A systematic review, including 18 studies and 4,256 patients aged ≥80 years admitted to the ICU with sepsis, reported ICU, hospital and 1-year mortality rates of 43%, 47% and 68%, respectively [3].…”
Section: Discussionsupporting
confidence: 86%
“…The previous VIP studies demonstrated that frailty is an important prognostic factor for short-term mortality in VIPs [1]. Sepsis as admission diagnosis appeared, after adjustment for organ dysfunction, not to be independently associated with shortterm outcome [2].…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…For our analysis, we used the Angus criteria to detect septic patients from a large electronic database of critically ill patients (18). This yielded a large cohort of patients with a relatively low absolute mortality compared to other cohorts evaluating old septic patients-for example, Ibarz et al (21) recently reported a 43% 30 day-mortality in very old septic patients. The use of the Angus criteria might therefore constitute a limitation to our analysis.…”
Section: Discussionmentioning
confidence: 99%